A Metallographic Investigation Of Transverse-Fissure Rails With Special Reference To High-Phosphorus Streaks - Discussion With Special Reference To High-Phosphorus Streaks - Discussion (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
G. F. COMSTOCK (author's reply to discussion *).-The discussion of this paper has been of such volume and interest as to constitute in itself a sufficient excuse for the paper, even though the paper itself may have been as much in error as some of its critics have maintained. Mr. Howard does not appear to realize some very practical facts that the opponents of his theory have advanced. Among these are: the coarsely crystalline fracture of the nucleus of a transverse fissure, so different from the smooth fatigue break around it; the occurrence of fissures in large numbers in certain heats or rollings of rails, while other heats or rollings do not develop them; and the much smaller proportion of transverse fissures found in rails rolled .from reheated blooms as compared with direct-rolled rails. These facts are not explained by Mr.